6281335119014 PENGARUH KOREKSI POSTUR TERHADAP PENURUNAN NYERI PINGGANG BAWAH PADA MAHASISWA SEBAGAI DAMPAK KEGIATAN PEMBELAJARAN SECARA VIRTUAL - Nia Kurniawati; Ahmad Syakib; Jerry Maratis (Jurnal Fisioterapi dan Kesehatan Indonesia, 2023)
Sitting for long hours during virtual learning will cause a musculoskeletal disorder in the lower spine which is commonly known as low back pain.Interventions that can be done to treat low back pain are through posture correction exercises, which are exercises to correct unstable muscles, bad posture and muscle pain caused by changes in posture by teaching someone good posture.Objective: To determine the effect of posture correction on reducing low back pain in college students. Research design: pre-experimental using a "one-group pretest-posttest" design.The research population was all Physiotherapy students at the Jakarta III Polytechnic of the Ministry of Health.The results of the sample count were 17 people.The independent variable in this study was the posture correction exercise intervention.The dependent variable is low back pain.This research was conducted in April – September 2022. Data collection used a low back pain assessment instrument and then provided posture correction interventions.Data analysis was performed using univariate and bivariate.The results of the statistical test proved that there was a significant difference in the average lower back pain in college students between before and after the intervention (p = 0.0001).Suggestion: So that students can practice Posture Correction regularly, so that lower back pain will be felt even less. Keywords: Posture Correction, low back pain.